Building a Future Generation of Entrepreneurs: An Experimental Study of the Integration of PBL and AI in Entrepreneurial - Hariyono, Hariyono (STAI Miftahul Ula Nganjuk, 2024)
This study investigates the effectiveness of integrating Project-Based Learning (PBL) with Artificial Intelligence (AI) in teaching entrepreneurship. Using a quasi-experimental design, the research involved two experimental groups: AI-assisted PBL and a control group (traditional PBL and lecture-based learning). The results indicate that, compared to the control group, the entrepreneurial skills of students were significantly enhanced through the integration of PBL and AI. The findings suggest that PBL and AI can be effective methods for teaching entrepreneurship. This study demonstrates that PBL combined with AI can help students develop the necessary skills and knowledge to become successful entrepreneurs.